Análisis de factibilidad tecno económica de un sistema para la producción de energía en el Eco-campus Cerros de la Universidad de América a partir de energías renovables. (2022)
In this project, whose purpose is to propose an electrical energy generation system through renewable energies for the Cerros Eco-Campus of the University of America, different alternatives are proposed based on photovoltaic solar energy, wind energy, bioenergy and a hybrid solar-bioenergy. Taking as resources the global horizontal radiation, the wind flow and the biomass from forest residues that can be produced in the Eco-Campus Cerros of the University of America. Initially, a theoretical framework is developed on the energy sources of interest, where the general aspects of each of them are shown. Subsequently, each of the production energy systems is dimensioned, thus establishing the configurations of each one of them through the selection of equipment and units, in this section the pertinent calculations are also presented to determine the configuration of these . Finally, based on the quantity and costs of the required equipment, the technical-economic aspects are considered with which the viability of each of the systems is evaluated. Initially, a theoretical framework is developed on the energy sources of interest, where the general aspects of each of them are shown. Subsequently, each of the production energy systems is dimensioned, thus establishing the configurations of each one of them through the selection of equipment and units, in this section the pertinent calculations are also presented to determine the configuration of these . Finally, based on the quantity and costs of the required equipment, the technical-economic aspects are considered with which the viability of each of the systems is evaluated.